ANALISIS PENGARUH LITERASI KEUANGAN, INKLUSI KEUANGAN DAN TEKNOLOGI KEUANGAN TERHADAP PENINGKATAN KINERJA UMKM LABUHANBATU - Tanjung, Soibatul Aslamiyah; Rambe, Bhakti Helvi; Rafika, Mulya (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to evaluate the influence of financial literacy, access to finance, and financial technology on the performance of MSMEs in Labuhanbatu. MSMEs have an important role to play in local economic development, but they still face various obstacles, particularly in financial management, access to financial services, and the application of financial technology. This study uses a quantitative method with a descriptive approach and multiple regression analysis. Data was obtained through a questionnaire distributed online to 97 MSME actors in Labuhanbatu who were selected using purposive sampling techniques. The findings of the study show that financial literacy, financial access, and financial technology, both individually and collectively, have a positive and significant impact on improving the performance of MSMEs in Labuhanbatu. Therefore, additional steps are needed to improve the financial literacy of business actors, expand access to formal financial services, and encourage the application of financial technology to support MSMEs to grow sustainably.